10th European immunogenicity platform open symposium on immunogenicity of biopharmaceuticals. Issue 1 (1st January 2020) - Tourdot, S.; Abdolzade-Bavil, A.; Bessa, J.; Broët, P.; Fogdell-Hahn, A.; Giorgi, M.; Jawa, V.; Kuranda, K.; Legrand, N.; Pattijn, S.; Pedras-Vasconcelos, J. A.; Rudy, A.; et al.
ABSTRACT: Therapeutic proteins and emerging gene and cell-based therapies are attractive therapeutic tools for addressing unmet medical needs or when earlier conventional treatment approaches failed. However, the development of an immune response directed against therapeutic agents is a significant concern as it occurs in a substantial number of cases across products and indications. The specific anti-drug antibodies that develop can lead to safety adverse events as well as inhibition of drug activity or accelerated clearance, both phenomena resulting in loss of treatment efficacy. The European Immunogenicity Platform (EIP) is a meeting place for experts and newcomers to the immunogenicity field, designed to stimulate discussion amongst scientists across industry and academia, encourage interactions with regulatory agencies and share knowledge and the state-of-the-art of immunogenicity sciences with the broader scientific community. Here we report on the main topics covered during the EIP 10th Open Symposium on Immunogenicity of Biopharmaceuticals held in Lisbon, 26–27 February 2019, and the 1-d training course on practical and regulatory aspects of immunogenicity held ahead of the conference. These main topics included immunogenicity testing, clinical relevance of immunogenicity, immunogenicity prediction, regulatory aspects, tolerance induction as a mean to mitigate immunogenicity and immunogenicity in the context of gene therapy.